Construction and validation of the My Medicines and Me Questionnaire for assessment of the self-reported side effects of psychotropic medication. (July 2015) - Ashoorian, Deena M.; Davidson, Rowan M.; Rock, Daniel J.T.; Dragovic, Milan; Clifford, Rhonda M.
Abstract : We aimed to construct and assess the psychometric properties of the My Medicines and Me Questionnaire (M3Q), a self-report side-effect questionnaire for mental health patients. Thirty individuals taking a psychotropic medication completed the M3Q side-effect checklist along with the Liverpool University Neuroleptic Side Effect Rating Scale. Thirty healthy comparison individuals also completed the M3Q checklist. Data were analyzed using factorial analysis. Psychometric evaluations including validity and reliability testing were carried out on the questionnaire's checklist. The original 54-item checklist of the M3Q was shortened to include only those items found to be significant in the factorial analysis. The revised 32-item checklist of the M3Q was found to be valid and reliable. The M3Q is a simple, valid and reliable questionnaire that can be used routinely in clinical practice for detecting bothersome side effects of a range of psychotropic medications. This will provide a platform for improved communication between the clinician and the patient. Abstract : Supplemental Digital Content is available in the text.